THE EFFECT OF ECONOMIC INDICATORS ON MOVEMENT OF COMPOSITE STOCK PRICE INDEX IN INDONESIA STOCK EXCHANGE - Hastina Febriaty (AIBPM Publisher, 2019)
The purpose of this study was to determine the effect of economic indicators such as the BI Rate, Inflation and Exchange Rate on the movement of the Composite Stock Price Index on the Indonesia Stock Exchange partially and simultaneously, and the variables that had the dominant influence on the Composite Stock Price Index on the Indonesia Stock Exchange. The data source used is secondary data taken from the Indonesia Stock Exchange, the Central Bureau of Statistics and Bank Indonesia from 2005 - 2018. The analysis technique used in this study is multiple linear regression analysis using e-views 10 program and testing classical assumptions. and using hypothesis testing simultaneously (F) and partial (t). The results of this study show partially the BI Rate has a negative and significant effect on the movement of the Composite Stock Price Index, Inflation has a positive and not significant effect on the movement of the Composite Stock Price Index while the Exchange has a positive and significant effect on the movement of the Composite Stock Price Index. While simultaneously the BI Rate, Inflation and Exchange Rate have a significant effect on the movement of the Composite Stock Price Index on the Indonesia Stock Exchange.